Iron-catalyzed dehydrogenation reactions and their applications in sustainable energy and catalysis - Balaraman, Ekambaram; Nandakumar, Avanashiappan; Jaiswal, Garima; Sahoo, Manoj K. (Catalysis Science & Technology, 2017)
Inspired by nature, chemists have designed new catalysts in the pursuit of selective bond activation and chemical transformations. Emergent biological systems often use earth-abundant first-row transition elements as catalytically active sites to facilitate specific and highly selective chemical processes. The design of a new catalytic system based on abundant and inexpensive catalysts, particularly the iron-based catalysts, for fundamentally significant synthetic transformations under environmentally benign conditions is an important paradigm in chemical synthesis. In recent times, iron-based catalytic systems have shown unprecedented reactivity in the acceptorless dehydrogenation reactions of feedstock chemicals, with the liberation of molecular hydrogen as the by-product, and have enabled greener chemical synthetic methods and alternative energy storage systems. Indeed, it has been demonstrated that the proper design of iron catalysts by judiciously choosing ligands, can aid in the development of new sustainable energy storage systems and catalysis. This tutorial review focuses on the recent development of iron-based dehydrogenation reactions of fundamentally important feedstock, as a route to sustainable chemical synthesis and energy storage applications. The emerging area of the iron-based dehydrogenation strategy provides an opportunity to make industrially applicable, cost-effective and environmentally benign catalytic systems.

Organo-photoredox catalyzed oxidative dehydrogenation of N-heterocycles - Sahoo, Manoj K.; Jaiswal, Garima; Rana, Jagannath; Balaraman, Ekambaram (Chemistry-A European Journal, 2017)
We report here for the first time the catalytic oxidative dehydrogenation of N-heterocycles by a visible-light organo-photoredox catalyst with low catalyst loading (0.1-1mol%). The reaction proceeds efficiently under base- and additive-free conditions with ambient air at room temperature. The utility of this benign approach is demonstrated by the synthesis of various pharmaceutically relevant N-heteroarenes such as quinoline, quinoxaline, quinazoline, acridine, and indole.

Room-temperature direct arylation of anilides under external oxidant-free conditions using CO2-Derived Dimethyl Carbonate (DMC) as a 'green' solvent - Sahoo, Manoj K.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Chemistryselect, 2017)
Here, an efficient catalytic protocol for direct C-H bond arylation of anilides under base- and external oxidant-free conditions is reported. This reaction proceeds readily at room temperature using CO2-derived dimethyl carbonate (DMC) as a green solvent under visible-light dual catalysis. Later, application of our strategy for the gram-scale synthesis of Boscalid has been successfully shown. An unprecedented unsymmetrical bis-arylation of anilides is also demonstrated under mild, redox-neutral conditions.

Unified strategy for silver-, base-, and oxidant-free direct arylation of C-H bonds - Sahoo, Manoj K.; Midya, Siba P.; Landge, Vinod G.; Balaraman, Ekambaram (Green Chemistry, 2017)
Here, we report a dual catalytic approach for room temperature direct arylation of C-H bonds with aryldiazonium salts as a simple aryl group donor, also working as an internal oxidant via C-N-2 bond cleavage. This unified strategy has been achieved by the synergistic combination of visible-light metal-free photoredox and palladium catalysis under silver-, base-and/or additive-free conditions. The broad substrate scope, functional group tolerance, excellent regioselectivity and redox-neutral conditions of this process make it attractive for the effective synthesis of a wide range of important N-heterocyclic commodities such as dibenzo [b,d]azepine, carbazole and phenanthridine.

Cobalt-catalyzed acceptorless dehydrogenative coupling of aminoalcohols with alcohols: direct access to pyrrole, pyridine and pyrazine derivatives - Midya, Siba P.; Landge, Vinod G.; Sahoo, Manoj K.; Rana, Jagannath; Balaraman, Ekambaram (Chemical Communications, 2018)
Here, the first example is reported of a new, molecularly defined SNS-cobalt(II) catalyst for the acceptorless dehydrogenative coupling (ADC) of unprotected amino alcohols with secondary alcohols leading to pyrrole and pyridine derivatives.

Photocatalysis enabling acceptorless dehydrogenation of diaryl hydrazines at room temperature - Sahoo, Manoj K.; Saravanakumar, Krishnasamy; Jaiswal, Garima; Balaraman, Ekambaram (ACS Catalysis, 2018)
Aromatic azo compounds are privileged structural motifs, and they exhibit a myriad of pharmaceutical as well as industrial applications. Here, we report a catalytic acceptorless dehydrogenation of diarylhydrazine derivatives to access a wide variety of aryl-azo compounds with the removal of molecular hydrogen as the sole byproduct. This distinctive reactivity has been achieved under dual catalytic conditions by merging the visible-light active [Ru(bpy)(3)](2+) as the photoredox catalyst and Co(dmgH)(2)(py)Cl as the proton-reduction catalyst. The reaction proceeds smoothly under very mild and benign conditions and operates at ambient temperature. This dual catalytic approach is highly compatible with many different functional groups and has a broad substrate scope. We have also demonstrated the reversible hydrogen storage and release phenomenon on hydrazobenzene/azobenzene couple to show the utility of these compounds as hydrogen storage materials. Further diversification of azobenzene was shown by a transition metal-catalyzed azo-group-directed ortho-C-H bond functionalization.
Keywords: acceptorless dehydrogenation; Azo benzene; dual catalysis; Hydrogen; photoredox catalysis

Reusable cobalt catalyst for reversible acceptorless dehydrogenation and hydrogenation of N-Heterocycles - Jaiswal, Garima; Subaramanian, Murugan; Sahoo, Manoj K.; Balaraman, Ekambaram (ChemCatChem, 2019)
<span style="color: rgb(42, 45, 53); font-family: "Source Sans Pro", Arial, Helvetica, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(248, 248, 248);">The development of robust catalytic systems based on basemetals for reversible acceptorless dehydrogenation (ADH) and hydrogenation of feedstock chemicals is very important in the context of ` hydrogen storage'. Herein, we report a highly efficient reusable cobalt-based heterogeneous catalyst for reversible dehydrogenation and hydrogenation of N-heterocycles. Both the ADH and the hydrogenation processes operate under mild, benign conditions.

Room temperature catalytic dehydrogenation of cyclic amines with the liberation of H-2 using water as a solvent - Sahoo, Manoj K.; Balaraman, Ekambaram (Green Chemistry, 2019)
Catalytic dehydrogenation of cyclic amines, in particular partially saturated N-heterocycles to N-heterocyclic arenes, with the removal of molecular hydrogen as the sole byproduct in water is reported. This dehydrogenation reaction proceeds smoothly under very mild and benign conditions and operates at room temperature. This distinctive reactivity has been achieved under dual catalytic conditions by merging the visible-light active [Ru(bpy)(3)](2+) as the photoredox catalyst and a newly synthesized cobalt complex as the proton-reduction catalyst. A detailed mechanistic study (control experiments, electrochemical studies, UV-visible experiments) is presented for the present dual catalysis.

Triazine functionalized porous covalent organic framework for photo-organocatalytic E-Z isomerization of olefins - Bhadra, Mohitosh; Kandambeth, Sharath; Sahoo, Manoj K.; Addicoat, Matthew; Balaraman, Ekambaram; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Visible light-mediated photocatalytic organic transformation has drawn significant attention as an alternative process for replacing thermal reactions. Although precious metal/organic dyes based homogeneous photocatalysts have been developed, their toxic and nonreusable nature makes them inappropriate for large-scale production. Therefore, we have synthesized a triazine and a keto functionalized nonmetal based covalent organic framework (TpTt) for heterogeneous photo catalysis. As the catalyst shows significant absorption of visible light, it has been applied for the photocatalytic uphill conversion of trans-stilbene to cis-stilbene in the presence of blue light-emitting diodes with broad substrate scope via an energy transfer process.

Convenient semihydrogenation of azoarenes to hydrazoarenes using H-2 - Sahoo, Manoj K.; Sivakumar, Ganesan; Jadhav, Sanjay; Shaikh, Samrin; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2021)
The high atom-economical and eco-benign nature of hydrogenation reactions make them much more superior to conventional reduction and transfer hydrogenation. Herein, a convenient and highly selective hydrogenation reaction of azoarenes using molecular hydrogen to access diverse hydrazoarenes is reported. The present catalytic method is general and operationally simple, and it operates under exceedingly mild conditions (room temperature and 1 atm of hydrogen pressure). The reusability of catalysts used in this method is also successfully demonstrated.